Surface and Catalytic Properties of the CoO/MgO System Doped with FeO - H.G. El-Shobaky; W.M. Shaheen; M. Mokhtar (Adsorption Science & Technology)
The surface and catalytic properties of pure and Fe 2 O 3 -doped Co 3 O 4 /MgO solids were investigated. The extent of loading was maintained at 38 wt% Co 3 O 4 and the amount of dopant varied between 1.2 wt% and 11.0 wt% Fe 2 O 3 . The pure and doped solids were prepared by calcination at 400–1000°C of pure and ferric nitrate-treated magnesium carbonate impregnated with cobalt nitrate solution. The samples thus obtained were examined by TG, DTA and XRD methods, nitrogen adsorption studies at −196°C and the catalysis of H 2 O 2 decomposition at 30–50°C. The results revealed that Fe 2 O 3 treatment of the Co 3 O 4 /MgO system followed by calcination at 400°C resulted in an increase in the particle size of the Co 3 O 4 and MgO phases, whilst the opposite effect was observed when the doped solids were calcined at 600°C. Doping of the Co 3 O 4 /MgO system followed by calcination at 400°C effected a measurable decrease in its BET surface area with the reverse effect being observed upon heating at 600°C. An increase in the calcination temperature of pure Co 3 O 4 /MgO up to 800°C brought about an abrupt decrease in the intensity of all the diffraction lines associated with the Co 3 O 4 phase. These disappeared completely upon heating the system at 900°C or 1000°C due to dissolution of the cobalt oxide in the MgO lattice to form a solid solution. A cobalt ferrite phase was detected in the variously doped solids calcined at 800–1000°C even when the initial solids had been treated with 2.4 wt% Fe 2 O 3 . This finding suggests that most of the ferrite phase produced was contained in the outermost surface layers of the treated samples. Treatment of the investigated system with Fe 2 O 3 followed by calcination at 400°C and 800°C led to a progressive decrease in the catalytic activity of the resulting solid due to an increase in the particle size (a decrease in the degree of dispersion) of the catalytically-activeconstituent, i.e. the Co 3 O 4 phase, and due to the conversion of Co 3 O 4 into a CoFe 2 O 4 phase, respectively. In contrast, doping followed by calcination at 600°C led to an increase in the catalytic activity of the resulting solid due to an effective decrease in the particle size of the Co 3 O 4 phase. Calcination of the Fe 2 O 3 -doped system at 400–800°C did not modify the mechanism of the catalyzed reaction but changed the concentration of active sites without changing their energetic nature.